PENERPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 7 PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Suryati '; Lazim N '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted because of the result of learning social study class III SDN 7 P.Pudu. From 30 Students who achieve KKm just 13 Students (43,33%) while students who didn’t complete 17 students (56,66%) with an average 65,66. The purpose of this research to inprove learning out comes IPS class III SDN 7 P.Pudu. with the application of learning models cooperative Make a Match results obtained by the average value of 67,66 basic score in creased in the first cycle of 21,23% to 79,67in the second cycle the average value of students also increased by 31,75% to 88,50 on the basic of completeness score IPS Student learning out comes is only 40% (finished).After the professor of applied learning model cooperative Make a Match. In the first cycle classical completeness increased 75% (not finished), the second cycle of classical completeness obtained are increased to increased 93,3%. Activities of teacher at the first meeting of 75% with both categories. The second meeting increased to 87,5% in both categories. In the second cycle increased to 91,675 with the category very well. At a meeting of the second of the second cycle. The activities of teacher increased to 95,835% with the category very well. Activities of students in the first cycle of the fisrt meeting activity students acquire a percentage of 79,17% in both categories. The second meeting of the fisrt cycle to 87,5% inboth categories. At the first meeting of the second cycle of student activity increased to 95,83%with the category very well, and at the second meeting of the second cycleincreased again to 95,83%with the category very well. Key Words: Make a Match, learning outcomes IPS